Case report: From anxiety disorders to psychosis, a continuum in transitional age youth? - Reis, Joana; Marchini, Simone; Nicolis, Hélène; Delvenne, Véronique (Frontiers in Psychiatry, 2022)
Introduction : To date, among individuals meeting ultra-high risk criteria for psychosis, the relationship between the presence of anxiety disorders and the risk of psychotic transition raises several unanswered questions. Case Description : This case report describes the clinical progression of a 17-year-old male initially presenting anxious symptoms meeting the DSM-V criteria for panic disorder. The patient also reported social withdraw, mild depressive symptoms, insomnia and fatigue. Over a 6 month period, a gradual onset of subthreshold psychotic symptoms suggested a prodromal phase of a psychotic disorder. Diagnostic Assessment and Therapeutic Intervention : A detailed assessment of UHR criteria for psychosis was performed. The overall level of social and occupational functioning was assessed by the SOFAS, which showed a 35% drop over a 12 months period. The CAARMS, has also been administered. The patient met the diagnostic criteria for UHR, APS group. The care plan included psychiatric follow-up, pharmacologic treatment, individual psychological follow-up and individual and familial psychoeducation. Over a 6 months period, the patient did not experienced a first psychotic episode and presented a partial improvement of psychotic symptoms. Conclusion : The DSM-V categorical approach does not seem to adapt well to early clinical presentations in transitional age youth. A transdiagnostic and dimensional approach allows to better identify at-risk patients of psychiatric disorders and implement early intervention strategies.